A Study of the Change of the Total Solar Radiation Above Baghdad City for the Period from 1985.1989 By Using Satellite Antenna Data - Tarish, O. J. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The solar radiation plays an important role on the energy balance of the earthatmosphere, which is the main source of energy.  Also the solar radiation is a main factor of all applications which use a solar energy as renewable energy source.  The purpose of this research is to study the monthly average changes for solar radiation for the period from 1985 to 1989 by using satellite Antenna Alignment from (NASA). The result shows that the monthly average radiation changes from one year to another because of the changing of it component of atmosphere, (gases, clouds and Aerosols) and as an enhancement for this conclusion, we compared the results with the monthly average radiation at clear atmosphere where the change was slight through the same period.